UZBEK LITERATURE - Mahmudxo‘jayeva Ziyodaxon Isomitdinovna (Ustozlar uchun, 2025)
Annotation: Uzbek literature has a rich history spanning over a thousand years, distinguished by its vibrant poetic and prose traditions. It encompasses oral folk creativity, including epics, songs, and satirical works, as well as the development of modern literary forms. Uzbek literature serves as an important reflection of the nation’s cultural heritage and historical experiences. This study explores the main periods, genres, and prominent writers of Uzbek literature.